Konsekuensi Hak Tanggungan Perjanjian Kredit Antara Kreditor dan Debitor - Martinus Al Ibrani Giga Taufano; Wilma Silalahi (LPPM Universitas Ekasakti Padang, 2024)
An agreement is the basis for the implementation of activities that bind the parties with an orientation towards the goals to be achieved. In the agreement, the parties agree to comply with the contents of the agreement, which gives birth to a legal relationship, this can be reformulated as,